2016
DOI: 10.5223/pghn.2016.19.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Intakes and Hair Mineral Contents of Young Children

Abstract: PurposeThis study was performed to evaluate the dietary nutrient intake status and hair mineral content of Korean young children.MethodsFifty-five children who visited Seoul National University Bundang Hospital were divided into three groups by age: infants, toddlers, and preschoolers. The 24-hour recall method was used to collect the food intake data of the subjects. Hair mineral analysis was conducted using a Mass Spectrometer. Serum iron, ferritin, and calcium were also measured.ResultsThe mean energy intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Results of an experiment that studied the hair of infants conducted by Kim et al [32] support the claim mentioned above with their observed concentrations being: Ca 548.1 mg/kg; Fe 6.5 mg/kg; Cu 0.4 mg/kg. More thorough studies of mechanisms causing the accumulation of certain elements are needed to further understand this problem.…”
Section: Discussionsupporting
confidence: 72%
“…Results of an experiment that studied the hair of infants conducted by Kim et al [32] support the claim mentioned above with their observed concentrations being: Ca 548.1 mg/kg; Fe 6.5 mg/kg; Cu 0.4 mg/kg. More thorough studies of mechanisms causing the accumulation of certain elements are needed to further understand this problem.…”
Section: Discussionsupporting
confidence: 72%
“…Hair Ca and Mg concentrations were also affected by diet, being higher in mixed diet fed dogs. Hair Ca concentration may reflect dietary Ca content (Ghorbani et al 2015 ; Kim et al 2016 ), and as many of the mixed diet fed dogs ate complete dry foods mixed with bone-containing raw foods, the total Ca content of their diets was probably higher. However, other dietary factors such as vitamin D and Mg can also raise hair Ca concentrations (Jeruszka-Bielak and Brzozowska 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, blood analysis indicates the current intake of elements (Jenkins 1979 ; Ahmad et al 2013 ). As blood is prone to fluctuations and homeostatic regulation, hair has been considered a more stable medium for reflecting dietary intake of elements in humans and other animals (Perry et al 1976 ; Ghorbani et al 2015 ; Kim et al 2016 ). During the last decade the interest in hair analysis among canine researchers has increased and it has become evident that not only dietary intake, but also age, sex, hair color, physiological status, health status, living environment, laboratory washing procedures, and in some cases breed, may also affect hair element concentrations in dogs (Chyla and Zyrnicki 2000 ; Park et al 2005 ; So et al 2016 ; Davies et al 2017b ; Sgorlon et al 2019 ; Chun et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For biological monitoring, readily accessible specimens reflecting average exposure to contaminants over a relatively long period of time are of particular importance. Hair analysis is thus used for detection of drugs in forensic medicine, detection of poisons in clinical and forensic toxicology, historical investigations, analysis of essential trace elements and mineral stores and evaluation of the internal exposure to pollutants in environmental medicine [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%